Hydrothermal Processing of Clarias gariepinus (Burchell, 1822) Filets: Insights on the Nutritive Value and Organoleptic Parameters - Okomoda, Victor Tosin (Vet Sci, 2020)
This study evaluated the effects of cooking for different hydrothermal-treatment durations (10, 20, 30 and 40 min) on the proximate composition, amino acid profile, fatty acid composition and organoleptic parameters of filets of African catfish Clarias gariepinus (Burchell, 1822). Filets of the fish were prepared from market size African catfish with similar breeding history. Parameters of the processed filet under the different hydrothermal durations were also compared against a raw–unprocessed control group except during organoleptic analysis. The results obtained revealed a significant increase in protein, fat and ash content until the 30th minute of hydrothermal processing (p ≤ 0.05). Beyond this processing time, protein and fat significantly reduced while ash remains unaffected. The same trend was observed for most essential/non-essential amino acids isolated as well as the prominent saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids. In all, the raw control group consistently recorded the least values of nutritional components. The perception of assessors was, however, found to be similar (p ≥ 0.05) in terms of organoleptic parameters regardless of the duration of the processing time of the filets. It was concluded that cooking the African catfish filet using the hydrothermal method should not be extended beyond 30 min.